1996
DOI: 10.1093/ajcn/64.5.748
|View full text |Cite
|
Sign up to set email alerts
|

Delayed tumor onset in transgenic mice fed an amino acid–based diet supplemented with red wine solids

Abstract: Increased consumption of vegetable foods (cereals, legumes, fruits) and some beverages (tea, cider, wine) is associated with reduced risk of cancer. Polyphenols in these foods and beverages are thought to be responsible, based on data from in vitro assays and from in vivo studies that used animals pretreated with carcinogen and given tea or polyphenol-spiked water to drink. We tested the hypothesis that dehydrated-dealcoholized red wine (wine solids), when consumed as part of a precisely defined complete diet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(49 citation statements)
references
References 32 publications
0
46
0
1
Order By: Relevance
“…In addition, the cancer preventive effect of grape seed extract was examined on the human prostate carcinoma DU145 cells possi-bly via apoptotic death (Agarwal et al, 2002). Though more rare in vivo, the solid fraction of red wine delayed the spontaneous onset of tumors in transgenic mice (Clifford et al, 1996). However, there was no study done on the effect of grape diet on the hepatocarinogensis.…”
Section: R Esults and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the cancer preventive effect of grape seed extract was examined on the human prostate carcinoma DU145 cells possi-bly via apoptotic death (Agarwal et al, 2002). Though more rare in vivo, the solid fraction of red wine delayed the spontaneous onset of tumors in transgenic mice (Clifford et al, 1996). However, there was no study done on the effect of grape diet on the hepatocarinogensis.…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…These polyphenolic compounds from grape or the polyphenol extracts have shown vitamin E sparing effect (Simonetti et al, 2002), and have been reported as chemopreventive agents. The polyphenol extracts protected from atherosclerosis progression in high cholesterol-fed rabbit aortic vessels (Yamakoshi et al, 1999), and the solid fraction of red wine delayed the spontaneous onset of tumors in mice (Clifford et al, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…They display a multitude of biological effects in vitro and in vivo after consumption of flavonoid-containing foods (Walle et al 1995;Clifford et al 1996;So et al 1996;Teissedre et al 1996;Da Silva et al 1998;Nidgikar et al 1998;Day et al 2000; Rein et al 2000a, b;Young et al 2000;Schramm et al 2001). Epidemiologic studies show strong associations between consumption of flavonoid-containing foods, especially wine, and reduced mortality from cardiovascular disease (St Leger et al 1979;Hertog et al 1993;Klatsky & Armstrong, 1993;Criqui & Ringel, 1994;Sasaki & Kesteloot, 1994;Grønbaek et al 1995;Hertog et al 1995;Renaud & de Lorgeril, 1992).…”
Section: Wine: Catechin: Catechin Metabolites: Urinary Excretion: Manmentioning
confidence: 99%
“…Much attention has been given to their antioxidant (Edenharder and Grü nhage, 2003) and anti-inflammatory properties, in vitro and in vivo (Calixto et al, 2003. In addition, some studies report antitumoral (Clifford et al, 1996) and hepatoprotective (Ferrá ndiz et al, 1994) action. Flavonoids inhibit cytokine release from RAW264.7 cells (Xagorari et al, 2002) and may modulate the increasing number of cellular processes involving redox reaction, including the regulation of tyrosine phosphatase activity (GametPayrastre et al, 1999).…”
mentioning
confidence: 99%